Foul Play in Sport as a Phenomenon Inconsistent with the Rules, yet Acceptable and Desirable: Ethical Conditions. A Contribution to Pedagogical Reflections - Kosiewicz, Jerzy (Physical education, sport and olympism from a pedagogical perspective, 2023)
The article has strictly a theoretical and non-empirical character. The author presents examples resulting from various observations. The aim of the paper is to present the causes, functions, and results of fouls, fouling, and foul play. Although fouls do not comply with the rules of games, the paper demonstrates that fouls are often used; they enjoy a quiet acceptance of the sporting world; they are tolerated and accepted; even more, they are often - more or less explicitly – desirable. The author employed the idiographic method (descriptive), that is, an approach typical for the general methodology applied in the non-empirical humanities and social sciences; the analytical method (referring to the British analytical philosophy);the nomothetic method (explanatory), the approach based on exegesis and hermeneutics of cultural texts utilized in order to create a closer understanding of the phenomenon of foul; the axiological method (evaluating of the use of foul);and the synthetic method, which was mainly used in the summary and the abstract. Author also applied a specific methodology, which refers to interpretationism based, in this case, on a genetic approach (referring to the sources and causes of phenomenon of foul), as well as on a realistic and empathetic approach.